Early Islam and the birth of capitalism - Koehler, Benedikt (Lexington Books, 2014)
Early Islam and the Birth of Capitalism proposes a strikingly original thesis—that capitalism first emerged in Arabia, not in late medieval Italian city states as is commonly assumed. Early Islam made a seminal but largely unrecognized contribution to the history of economic thought; it is the only religion founded by an entrepreneur. Descending from an elite dynasty of religious, civil, and commercial leaders, Muhammad was a successful businessman before founding Islam. As such, the new religion had much to say on trade, consumer protection, business ethics, and property. As Islam rapidly spread across the region so did the economic teachings of early Islam, which eventually made their way to Europe.